Bony contact area and displacement of the temporomandibular joint after high-oblique and bilateral sagittal split osteotomy: a computer-simulated comparison. Issue 3 (April 2016) - Möhlhenrich, Stephan Christian; Kamal, Mohammad; Peters, Florian; Fritz, Ulrike; Hölzle, Frank; Modabber, Ali
Abstract: The most common way to move the mandible during orthognathic surgery is by bilateral sagittal split osteotomy (BSSO). The high-oblique sagittal split osteotomy (HSSO) is an alternative, although its use is limited by potential complications, mainly to do with the position of the condyle and reduced contact with bone. The aim of this study was to find out the optimal intercondylar distance and area of contact with the surface of the bone for mandibular advancement and setback in BSSO and HSSO. Data from computed tomographic (CT) images from 40 patients were loaded into special planning software, and virtual operations done for mandibular advancement and setback at 3, 5, 8, and 10 mm using BSSO and HSSO, which resulted in 640 individual mandibular displacements. The resultant area of bony contact and intercondylar distance were calculated by the software. The mean (SD) areas of contact with the bony surface after 10 mm advancement for HSSO and BSSO were 193.94 (63.76) mm 2 and 967.92 (229.21) mm 2, respectively, and after 10 mm setback 202.64 (62.30) mm 2 and 1108.86 (247.38) mm 2 . The mean corresponding intercondylar distance after maximum advancement were 86.76 (6.40) mm and 86.59 (6.24) mm, and after maximum setback 74.90 (5.73) mm and 73.06 (6.06) mm. There were significant differences between the two for the area of contact with the surface at each displacement distance (p < 0.001), but not for intercondylar distance. A larger area of bony contact can be expected at any displacement distance for BSSO, so the changes in intercondylar distance should not be considered when deciding which osteotomy to select.